PENGENALAN BUDAYA BALI MENGGUNAKAN MEDIA PEMBELAJARAN GAMELAN GONG KEBYAR DI SD RAJ YAMUNA DENPASAR - Dwi Putra Githa; I Putu Arya Dharmaadi; Desy Purnami Singgih Putri; Dewa Made Sri Arsa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Bali Island is an island which is famous for its unique art and culture and customs. One of the cultural heritages is still preserved and often used until now is Balinese Gamelan. Gamelan Gong Kebyar really needs to be preserved, especially taught to young people. However, not all schools or village halls have Gamelan Gong Kebyar instruments. The problem of limited access which is a core problem can be overcome by the use of information technology which has recently developed very rapidly, namely developing a learning media about the art of Gamelan Gong Kebyar. The learning media that are built are in the form of a Virtual Reality Application for the Introduction and Learning of Traditional Balinese Gong Kebyar Gamelan Music Instruments based on Android. This application displays gamelan instruments such as Ugal, Gangsa, Kajar / Petuk, Kendang, Gong, Jegogan, Ceng-Ceng, Kompompong, Reyong, and Kantil in the form of virtual reality in 3-dimensional objects. By utilizing this application, it is hoped that generations of children will be more interested and easier to learn Gamelan Gong Kebyar.